The Influence of Organizational Culture and Altruism on the Performance of Employees of PT. XYZ - Desti Apriliani; Muhamad Alwi; Dharliana Hardjowikarto (International Journal Labs, 2026)
Amid increasingly intense organizational competition, employee performance has become a crucial determinant of organizational effectiveness and sustainability. A strong organizational culture can guide employee behavior, strengthen work commitment, and create alignment between individual actions and organizational goals. In addition, altruism, as a voluntary willingness to help colleagues without expecting personal rewards, is also considered an important behavioral factor in supporting workplace productivity. This research aims to examine the influence of organizational culture and altruism on employee performance. This study employs a quantitative approach with a causal-associative design. The population in this study consists of all 140 employees of PT. XYZ, with a sample of 104 respondents selected using a proportionate stratified random sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression. The results of the t-test showed that organizational culture had a positive and significant effect on performance (t-count = 3.038 > t-table = 1.65993). Similarly, altruism had a positive and significant effect on performance (t-count = 4.276 > t-table = 1.65993). Simultaneously, the results of the F-test showed that organizational culture and altruism had a significant effect on employee performance (F-count = 13.081 > 3.09), with a 20.6% contribution to performance variance. These results indicate that strengthening organizational cultural values and voluntary helping behaviors among employees is essential to increase overall company productivity.